Fungi, host immune response, and tumorigenesis - Elaskandrany, Miar; Patel, Rohin; Patel, Mintoo; Miller, George; Saxena, Deepak; Saxena, Anjana (American journal of physiology: Gastrointestinal and liver physiology, 2021)
Advances in -omics analyses have tremendously enhanced our understanding of the role of the microbiome in human health and disease. Most research is focused on the bacteriome, but scientists have now realized the significance of the virome and microbial dysbiosis as well, particularly in noninfectious diseases such as cancer. In this review, we summarize the role of mycobiome in tumorigenesis, with a dismal prognosis, and attention to pancreatic ductal adenocarcinoma (PDAC). We also discuss bacterial and mycobial interactions to the host’s immune response that is prevalently responsible for resistance to cancer therapy, including immunotherapy. We reported that the Malassezia species associated with scalp and skin infections, colonize in human PDAC tumors and accelerate tumorigenesis via activating the C3 complement-mannose-binding lectin (MBL) pathway. PDAC tumors thrive in an immunosuppressive microenvironment with desmoplastic stroma and a dysbiotic microbiome. Host-microbiome interactions in the tumor milieu pose a significant threat in driving the indolent immune behavior of the tumor. Microbial intervention in multimodal cancer therapy is a promising novel approach to modify an immunotolerant (“cold”) tumor microenvironment to an immunocompetent (“hot”) milieu that is effective in eliminating tumorigenesis.